Young People : Global and Regional Burden of Disease - Gordillo-Tobar, Amparo; Calvo, Nashira; Quinaln-Davidson, Meaghen (World Bank, Washington, DC, 2020)
Adolescence and youth are periods of opportunities but also of increasing vulnerability defined by social and political factors. Early marriages and risky behaviors are strongly associated with inequalities of income, education, gender, and ethnicity, all of which can increase young people's susceptibility to poor health and well-being throughout their lifecycle. Adolescent health is more important than ever, given that the world contains the largest cohort in history of young people aged between 10 and 24 years old. The challenges affecting the livelihood of young people are reflected in their burden of disease (BoD). A better understanding of the BoD for this generation of adolescents and youths can help to reveal what measures health systems should be taking to curb behavior related to health risks, for example, eating patterns, physical activity and weight, sexual behavior, the use of psychoactive substances, and transport-related injuries.